GAMBARAN KEJADIAN IBU HIPERTENSI DALAM KEHAMILAN DENGAN COVID-19 DI RSUD ULIN BANJARMASIN PERIODE MEI 2020-JUNI 2021 - Rahayu Arumningtyas; Ferry Armanza; Siti Wasilah; Hariadi Yuseran; Lena Rosida (Homeostasis, 2022)
Hypertension in pregnancy is one of the most common causes of maternal death in Indonesia as well as in other developed countries such as the United States. The cause of preeclampsia is currently uncertain, but there are several risk factors that can increase the occurrence of preeclampsia. Coronavirus disease 19 (COVID-19) is caused by the Severe Acute Respiratory Syndrome Coronavirus-2 (SARS CoV-2). Pregnant women and hypertension are factors that can increase the risk of COVID-19. If not treated properly, hypertension in pregnancy can cause maternal and fetal morbidity and mortality. The purpose of this study was to describe the incidence of maternal hypertension in pregnancy with COVID-19 based on age, parity, gravida, history of preeclampsia, and education at Ulin Hospital Banjarmasin for the period May 2020-June 2021. This research method was descriptive with data collection through medical records. patient. The sampling technique used is total sampling. The subjects of this study amounted to 88 patients. This study shows preeclampsia is the type of hypertension in pregnancy with COVID-19 being the most common, which was 57 patients (64.7%). Most of the patients were in the age range of 20-35 years, as many as 52 patients (59.3%). Based on parity, most of the cases occurred in mothers with multilipara as many as 39 patients (44.3 %). Gravida was found mostly in mothers with multigravida as many as 63 patients (71.6%). Based on a history of preeclampsia, patients who did not have a history of preeclampsia were found to be more than patients who had a history of preeclampsia, namely as many as 52 patients (59.1%) and the majority of patients' education at the high school level, which was 29 patients (32.9%).